Actual Issues of Reform of Georgian National Security Sector’s Accountability and Oversight System - Alapishvili, Levan (Journal of Law, 2024)
By its nature and specific obligations, the security assurance system contradicts external control, oversight and accountability principles, because its significant part and decisions are related to secret activities and documents. Therefore, in the democratic governance of national security and oversight of the activities of security institutions, the role of the Parliament, as the highest standing political authority, acting for the interests of the people is extremely important. The Parliament, as the highest legislator sets scopes for the activity, accountability and control of security institutions. Efficient parliamentary oversight increases the quality of accountability of security institutions and protects the society from arbitrary, inappropriate or repressive governance. A democratic governance system requires efficient oversight of secret activities. This objective can be achieved, first of all, via independent, powerful institutions and the system that provides oversight of personal data collection. The oversight is not limited to parliamentary oversight only, the development of governmental, judicial and independent institutions is not less important. This Paper presents experience and analysis of the development of the oversight system over the activities of the security institutions of Georgia and other democratic countries. The Paper provides the comparative analysis of experiences of Georgian and foreign countries about the oversight of the activities of security institutions and personal data protection in secret activities. The Paper puts some issues for discussion concerning the actual matters of the reform of the control system over the activities of security institutions, providing the considerations about establishing new, independent oversight institutions.